Persepsi Siswa terhadap Proses Belajar Mengajar Guru Ekonomi Menggunakan Kurikulum 2013 pada SMA Kristen YPKPM Ambon - Soukotta, Juliet; Salong, Amjad; Manuhuttu, Silvia (Jurnal Pendidikan Ekonomi, 2023)
This study aims to describe students’ perceptions of the teaching and learning process conducted by economics teachers using the 2013 Curriculum at YPKPM Christian Senior High School Ambon, specifically among Grade X IIS students. A descriptive quantitative approach was employed, using a closed-ended questionnaire distributed to 20 respondents. The instrument was developed based on indicators covering lesson planning, implementation, and evaluation. The results show that students’ perceptions are generally positive. Teachers are considered capable of designing lessons aligned with core competencies, applying various methods, and delivering material clearly and systematically. During implementation, teachers foster a conducive learning environment and encourage active student participation. However, some students noted that the evaluation methods did not fully reflect individual abilities due to the dominance of multiple-choice questions. The study recommends improving evaluation methods, incorporating more interactive digital media, and enhancing teacher training to optimize the 2013 Curriculum implementation. These findings are expected to serve as input for educators and policymakers in improving the quality of economics education